Kuantifikasi Inversi Galaktomanan Kolang-Kaling (Arenga pinnata Merr.) dengan Iodometri - Nilsya Febrika Zebua Zebua; Sumardi; Suprianto; Putri Addina (Jurnal Indah Sains dan Klinis, 2024)
Background: Kolang-Kaling (Arenga pinnata Merr.) belongs to the Arecaceae family as a source of natural polysaccharides in the form of galactomannan which is usually used as an additional ingredient. Objective: The study was aimed at determining whether galactose-mannose from Kolang-Kaling (GKK) could be separated using chromatography and its levels using the iodometry method. Method: Extraction of galactomannan using distilled water as a solvent. Purification by Paper Chromatography using WEB [Water: Ethanol: Butanol] mobile phase; WAB [Water: Acetate: Butanol]; CH3COOH 10.0% and 50.0%; CA 10.0% and 20.0%. Purification by TLC uses a variation of the EA: H mobile phase. Results: The GKK extraction yield was 18,5 g (3.7%). The levels before and after inversion were 85.53% and 90.23% with a galactose-mannose standard of 94.52%. Conclusion: Galactomannan can be obtained from Kolang-Kaling extraction and its levels are determined using the iodometry method